The increasing of professional-applied physical preparedness and diagnostics of risk’s level appetite and neuro-psychological stability of cadets from educational institutions of the Ministry for Emergency Situations of the Republic of Belarus - Chumila Евгений (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
The article presents the specifics of rescuers’ professional activity. The method is described the improving professional-applied physical preparedness of cadets from educational establishments of the MES of the Republic of Belarus, which is based on the application of multifunctional training complex of modeling emergencies’ hazards – strips of military and psychological preparation. The dynamic is showed of physical development, physical and professional preparedness of cadets from the Institute for Command Engineers of the MES of the Republic of Belarus at the beginning and end of the educational experiment. There is reliable information, which is defining the efficiency of the proposed method of training exercises thanks to the multifunctional training complex. The psychological diagnosis’ results of testers from control and experimental groups are presented.